The role of binocular vision in the control and development of visually guided upper limb movements. (30th January 2023) - Niechwiej-Szwedo, Ewa; Colpa, Linda; Wong, Agnes
Abstract : Vision provides a key sensory input for the performance of fine motor skills, which are fundamentally important to daily life activities, as well as skilled occupational and recreational performance. Binocular visual function is a crucial aspect of vision that requires the ability to combine inputs from both eyes into a unified percept. Summation and fusion are two aspects of binocular processing associated with performance advantages, including more efficient visuomotor control of upper limb movements. This paper uses the multiple processes model of limb control to explore how binocular viewing could facilitate the planning and execution of prehension movements in adults and typically developing children. Insight into the contribution of binocularity to visuomotor control also comes from examining motor performance in individuals with amblyopia, a condition characterized by reduced visual acuity and poor binocular function. Overall, research in this field has advanced our understanding of the role of binocular vision in the development and performance of visuomotor skills, the first step towards developing assessment tools and targeted rehabilitation for children with neurodevelopment disorders at risk of poor visuomotor outcomes. This article is part of a discussion meeting issue 'New approaches to 3D vision'.